Percepção ambiental de estudantes em regimes de tempo regular e integral: estudo em uma escola municipal de João Pessoa-PB - Sousa, Larisse Lima de (2014)
Children and adolescents spend part of their time in school environments; within the “Projeto Mais Educação” (PME) it represents a minimum of 7 hours per day. In the city of João Pessoa, by the end of 2013, from the 11 standard schools opened, six had joined this project, working in mixed system: some students in part-time and others in full-time. This situation led to the development of this research, as it raised a questioning on how these two groups perceived the school environment. The main hypothesis is that there are differences in mental representation between the groups and that full-time students perceive the school environments in greater quantity and level of detail. One of the standard schools that joined the PME from the municipal network of the city of João Pessoa was chosen to test the hypothesis. The ages of the 90 students that took part on the research ranged from 8 to 16 years old. The methodology followed these steps: I- exploratory visit to the school; II- semi-structured interview with the principal; III- description of the school’s environmental aspects (thermal, acoustic, luminous and furniture); IV- making of themed drawings by the students; V- survey with the students; VI- discussing the collected information. The results showed no significant differences between the quantity of environments perceived by students of the two regimes (t (88) = 0.74; p-value> 0.05). In general, students establish positive relationships with school environments, with preference for the multi-sport gymnasium that act as a courtyard because it is where they gather during playtime. Despite this, the recurrent representation of grids in the drawings evidences a sense of imprisonment. The computer classroom is mentioned, but the lack of Internet access implies a barrier that makes it unusable. Students proposed improvements to the existing environments along with the creation of game areas, playground and swimming pool. At the end of the research, besides the feedback to the school, recommendations have been put to reduce the problems encountered and to be forwarded to the municipal Department of Education.